Teaching the history of scientific racism: A critical imperative for anti-racist pedagogy - Gillies, Carmen (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
Drawing from a review of literature that has explored the history of scientific racism, this article considers how understanding the history of race, as an 18th- and 19th-century invention of Western Europe and the United States, can enhance Canadian anti-racist teacher education. I begin with a review of key conceptual building blocks of race — racial categories, racial hierarchies, White male intellectual superiority, and racial purity — and then outline pivotal historical stages that led acclaimed researchers to denounce race science in the mid-20th century. To conclude, I draw from anti-racist theory to discuss implications for present-day Canadian teacher education regarding who benefits from racism, who can be racist, school-based deficit and essentialist racist practices, and K–12 curricular connections.